2021
DOI: 10.1016/j.ijrobp.2020.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Pain Response After Stereotactic Body Radiation Therapy Versus Conventional Radiation Therapy in Patients With Bone Metastases—A Phase 2 Randomized Controlled Trial Within a Prospective Cohort

Abstract: Pain response after conventional external beam radiation therapy (cRT) in patients with painful bone metastases is observed in 60% to 70% of patients. The aim of the VERTICAL trial was to investigate whether stereotactic body radiation therapy (SBRT) improves pain response. Methods and Materials: This single-center, phase 2, randomized controlled trial was conducted within the PRESENT cohort, which consists of patients referred for radiation therapy of bone metastases to our tertiary center. Cohort participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 26 publications
1
71
0
Order By: Relevance
“…Higher rates of pain response have also been corroborated in non-spine bone metastasis treated with SBRT compared to MFRT (14). In contrast, other studies showed in localized spine metastases that pain control was not improved following SBRT (15,16). This study presents the first evaluation of the efficacy of SBRT for palliation of intra-thoracic tumors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Higher rates of pain response have also been corroborated in non-spine bone metastasis treated with SBRT compared to MFRT (14). In contrast, other studies showed in localized spine metastases that pain control was not improved following SBRT (15,16). This study presents the first evaluation of the efficacy of SBRT for palliation of intra-thoracic tumors.…”
Section: Discussionmentioning
confidence: 54%
“…Most literature assessing the efficacy of SBRT has been in the curative or oligometastatic setting (4)(5)(6)(7)(8)(9)(10)(11)(12). In the realm of spinal and bone metastases, recent studies have assessed the role of SBRT in the palliative setting with overall mixed results in pain relief (13)(14)(15)(16)(17). However, no studies have yet explored the role of palliative SBRT in thoracic malignancies.…”
Section: Original Articlementioning
confidence: 99%
“…Furthermore, there was a significant association between single fraction SBRT and the development of pseudo-progression [ 26 ]. The so far published randomized trials comparing SBRT versus conventional radiotherapy have not reported the rates of pseudo-progression [ 12 , 27 , 28 ]. The SPINO group defined any new or progressive tumor within the epidural space as local progression [ 13 ], but we have recently published a case report showing clear epidural involvement on radiological images after spine SBRT, yet histologically without tumor cells in the epidural space [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as they chose the single fraction SBRT with 24 Gy, the rates of new pathological fracture were high in that study, with 8.7% and 27.8% at 3 and 6 months respectively [ 12 ]. Another randomized phase 2 trial from the Netherlands compared SBRT versus conventional radiotherapy for bone metastases using different fractionations [ 28 ]. SBRT group did not show significant pain improvement, but because of selective dropout, this trial was underpowered to detect the difference in pain response [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using this design, the intervention study is performed within a prospective cohort. Compared to conventional RCTs, the TwiCs design can lead to more efficient patient recruitment, generalizability of results may be improved, and TwiCs allows evaluation of patients' acceptability of the intervention [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%